Rosacea: diagnostics and treatment - A. A. Kubanova; Yu. B. Makhakova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The authors present current data from the literature relating to major characteristics and efficacy of methods of non-invasive diagnostics of rosacea (dermatoscopy, dopplerography, ultrasound scanning, confocal laser scanning microscopy) as well as aspects of a systemic external therapy, laser therapy and use of IPL systems in the treatment of patients suffering from rosacea.